AB0384 MEDICATION USE IN SYSTEMIC LUPUS ERYTHEMATOSUS – DATA FROM A MULTICENTRE COHORT STUDY. (2nd June 2020) - Kandane-Rathnayake, R.; Louthrenoo, W.; Luo, S. F.; Wu, Y. J.; Chen, Y. H.; Golder, V.; Lateef, A.; Cho, J.; Navarra, S.; Zamora, L.; Hamijoyo, L.; Sockalingam, S.; et al.
Abstract : Background: In the absence of evidence-based treatment guidelines, medication use in SLE is highly variable. Low rates of remission and lupus low disease activity state (LLDAS) suggest that suboptimal responses to standard medications, which include glucocorticoids (GC), anti-malarial (AM) drugs and immunosuppressive (IS) agents, are common. Understanding the utility of current medications will facilitate the selection of patients for advanced therapies as they emerge. Objectives: To examine medication use patterns in a large multicentre SLE cohort. Methods: We used 2013-18 data from the Asia Pacific Lupus Collaboration (APLC) cohort in which disease activity (SLEDAI-2K) and medication details were captured at every visit. LLDAS was defined as in Golder et al., 2019 (1). We examined the use of medication (med) categories (GC &/or AM &/or IS) by SLE disease activity and LLDAS at the visit level. Additionally, we performed Cox regression analyses to determine the time-to-discontinuation of meds stratified by SLE disease activity, ranked by time-adjusted mean SLEDAI-2K, and by percent-time spent in LLDAS. Results: We analysed data from 19, 804 visits of 2, 860 patients. We observed 8 med categories: no meds; GC, AM or IS only; GC+AM; GC+IS; AM+IS and GC+AM+IS (triple therapy). Triple therapy was the most frequent med pattern (32%); single agents were used in 21% of visits and biologicals in only 3%. Among visits where SLEDAI-2K was ≥10, triple therapy was used in 46%, with median [IQR] GC dose 10 [6, 24] mg/day; in contrast, among visits with SLEDAI-2K≤4 triple therapy was used in 28% (p<0.01). Patients in LLDAS received less combination therapy than those who were not in LLDAS. Med persistence (survival analysis) varied widely, with lowest survivals for IS. Patients with time-adjusted mean SLEDAI-2K ≥10 had lower discontinuation of GC and higher discontinuation of IS including azathioprine, leflunomide and cyclosporine (Table 1 ). In contrast, increased time in LLDAS was associated with reduced discontinuation of AM and azathioprine. Conclusion: In a large multicentre SLE cohort, most patients were receiving combination treatment. AM treatment survival was high and associated with low disease activity, GC survival was high and associated with high disease activity, while IS survival was low. Patients with high disease activity received more medication combinations but had reduced IS survival. These data suggest ongoing unmet need for improved medications for treatment of SLE. Reference: Golder, V., et al Lancet Rheum. 2019 1(2):e95-102 Disclosure of Interests: Rangi Kandane-Rathnayake Grant/research support from: The APLC has received financial (non-restricted educational) grants from AstraZeneca, Bristol Myers Squibb, GlaxoSmithKline, Janssen, EMD Serono, Eli Lilly and UCB for the LLDAS Validation Study., Worawit Louthrenoo: None declared, Shue Fen Luo: None declared, Yeong-Jian Wu Consultant of: Pfizer, Lilly, Novartis, Abbvie, Roche, Speakers bureau: Lilly, Novartis, Yi-Hsing Chen Grant/research support from: Taiwan Ministry of Science and Technology, Taiwan Department of Health, Taichung Veterans General Hospital, National Yang-Ming University, GSK, Pfizer, BMS., Consultant of: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas, Inova Diagnostics, UCB, Agnitio Science Technology, United Biopharma, Thermo Fisher, Gilead., Paid instructor for: Pfizer, Novartis, Johnson & Johnson, Roche, Lilly, Astra& Zeneca, Sanofi, Astellas, Agnitio Science Technology, United Biopharma., Speakers bureau: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas, Inova Diagnostics, UCB, Agnitio Science Technology, United Biopharma, Thermo Fisher, Gilead., Vera Golder: None declared, Aisha Lateef: None declared, Jiacai Cho: None declared, Sandra Navarra Speakers bureau: Astellas, Novartis, Pfizer, Johnson & Johnson, Abbvie, Leonid Zamora: None declared, Laniyati Hamijoyo Speakers bureau: Pfizer, Novartis, Tanabe, Abbot, Dexa Medica, Roche, Sargunan Sockalingam: None declared, Yuan An: None declared, Zhanguo Li: None declared, Yasuhiro Katsumata: None declared, masayoshi harigai Grant/research support from: AbbVie Japan GK, Ayumi Pharmaceutical Co., Bristol Myers Squibb Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Nippon Kayaku Co., Ltd., and Teijin Pharma Ltd. MH has received speaker's fee from AbbVie Japan GK, Ayumi Pharmaceutical Co., Boehringer Ingelheim Japan, Inc., Bristol Myers Squibb Co., Ltd., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Eli Lilly Japan K.K., GlaxoSmithKline K.K., Kissei Pharmaceutical Co., Ltd., Oxford Immuotec, Pfizer Japan Inc., and Teijin Pharma Ltd. MH is a consultant for AbbVie, Boehringer-ingelheim, Kissei Pharmaceutical Co., Ltd. and Teijin Pharma., Yanjie Hao: None declared, Zhuoli Zhang: None declared, Madelynn Chan: None declared, Jun Kikuchi: None declared, Tsutomu Takeuchi Grant/research support from: Eisai Co., Ltd, Astellas Pharma Inc., AbbVie GK, Asahi Kasei Pharma Corporation, Nippon Kayaku Co., Ltd, Takeda Pharmaceutical Company Ltd, UCB Pharma, Shionogi & Co., Ltd., Mitsubishi-Tanabe Pharma Corp., Daiichi Sankyo Co., Ltd., Chugai Pharmaceutical Co. Ltd., Consultant of: Chugai Pharmaceutical Co Ltd, Astellas Pharma Inc., Eli Lilly Japan KK, Speakers bureau: AbbVie GK, Eisai Co., Ltd, Mitsubishi-Tanabe Pharma Corporation, Chugai Pharmaceutical Co Ltd, Bristol-Myers Squibb Company, AYUMI Pharmaceutical Corp., Eisai Co., Ltd, Daiichi Sankyo Co., Ltd., Gilead Sciences, Inc., Novartis Pharma K.K., Pfizer Japan Inc., Sanofi K.K., Dainippon Sumitomo Co., Ltd., Fiona Goldblatt: None declared, Sean O'Neill: None declared, Chetan Karyekar Shareholder of: Johnson & Johnson, Consultant of: Janssen, Employee of: Janssen Global Services, LLC. Previously, Novartis, Bristol-Myers Squibb, and Abbott Labs., Jennifer H. Lofland Employee of: Janssen, Sang-Cheol Bae: None declared, Chak Sing Lau: None declared, Alberta Hoi: None declared, Mandana Nikpour: None declared, Eric F. Morand Grant/research support from: AstraZeneca, Consultant of: AstraZeneca, Speakers bureau: AstraZeneca